2020
DOI: 10.1002/nbm.4390
|View full text |Cite
|
Sign up to set email alerts
|

An information‐based comparison of diffusion attenuation models in normal and inflamed bone marrow

Abstract: Diffusion‐weighted imaging has received attention as a method for characterizing inflammatory exudates in bone marrow in immune‐mediated inflammatory diseases and reveals an increase in diffusivity in regions of bone marrow oedema. Various models of diffusion attenuation have been investigated but the model providing the best description of tissue pathophysiology in regions of marrow oedema is unknown. Determining the most appropriate model is an important step towards protocol optimization and the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Bray et al found no significant difference in f and D * between normal and inflamed marrow. In addition, their research showed that the enhancement with contrast in areas of BME may be due to an increase in capillary permeability instead of perfusion ( 42 ). Parameters derived from DCE-MRI ultimately reflect microvascular structure and function, which means that the perfusion mechanism indicated by K trans and perfusion parameters derived from IVIM DWI is not exactly the same.…”
Section: Discussionmentioning
confidence: 99%
“…Bray et al found no significant difference in f and D * between normal and inflamed marrow. In addition, their research showed that the enhancement with contrast in areas of BME may be due to an increase in capillary permeability instead of perfusion ( 42 ). Parameters derived from DCE-MRI ultimately reflect microvascular structure and function, which means that the perfusion mechanism indicated by K trans and perfusion parameters derived from IVIM DWI is not exactly the same.…”
Section: Discussionmentioning
confidence: 99%
“…While ADC measurements provide a useful summary measure of tissue diffusion, more sophisticated models of diffusion such as intravoxel incoherent motion (IVIM), can separate the contributions of tissue diffusivity from the effect of perfusion 32–35 and may provide a more comprehensive description of the MRI signal than standard monoexponential models. 35 …”
Section: Quantitative Mri Techniques and Biomarker Development In Axspamentioning
confidence: 99%
“…SpA is characterised by a range of abnormalities which include subchondral bone marrow oedema near the sacroiliac joint (SIJ) margins [39]. These inflammatory lesions, which can be subtyped as either 'active' or 'chronic', have been found to be well-described by the intravoxel incoherent motion (IVIM) dMRI model [40], with IVIM parameter estimates being sensitive to changes in pathology [38,41].…”
Section: -Clinical Contextmentioning
confidence: 99%
“…We identified two clinical datasets for which classification task performance was either published or could be computed: an in-house 28-patient dataset ("Bray") [41] split across two SpA subtypes and analysed for one task, and an external 41-patient dataset ("Zhao") [38] split across three SpA subtypes, which was not available for primary analysis but which reported ROC/AUC for three tasks.…”
Section: -Validation (E1)mentioning
confidence: 99%
See 1 more Smart Citation